On Generalized Simple P-injective Rings - Nazar Shuker; Raida Mahmood (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this work, we study generalized simple P-injective rings. New properties of such rings are given, and a characterization of division rings and strongly regular rings in terms of GSP rings is obtained.